2023
DOI: 10.1002/jcp.31076
|View full text |Cite
|
Sign up to set email alerts
|

Decoding hepatocarcinogenesis from a noncoding RNAs perspective

Abstract: Being a leading lethal malignancy worldwide, the pathophysiology of hepatocellular carcinoma (HCC) has gained a lot of interest. Yet, underlying mechanistic basis of the liver tumorigenesis is poorly understood. The role of some coding genes and their respective translated proteins, then later on, some noncoding RNAs (ncRNAs) such as microRNAs have been extensively studied in context of HCC pathophysiology; however, the implication of long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs) in HCC is indeed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 239 publications
(220 reference statements)
0
12
0
Order By: Relevance
“…Alternatively, lncRNAs can be classified according to their functional role [ 17 ]. As already indicated, lncRNAs have a significant regulatory function, modulating the activity of genes, RNAs, proteins, organelles, and nuclear condensates [ 21 , 22 ].…”
Section: Roles and Functions Of Lncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, lncRNAs can be classified according to their functional role [ 17 ]. As already indicated, lncRNAs have a significant regulatory function, modulating the activity of genes, RNAs, proteins, organelles, and nuclear condensates [ 21 , 22 ].…”
Section: Roles and Functions Of Lncrnasmentioning
confidence: 99%
“…Members of this class have transcripts larger than 200 nucleotides and are important regulators [ 15 , 16 ]. LncRNAs can also be divided into subclasses [ 17 , 18 ]. According to one of these classifications, the genomic location of ncRNAs can result in intergenic, intronic, sense, and antisense lncRNAs [ 9 , 19 , 20 ], as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…8 LncRNAs have emerged as one of the most interesting components of the transcriptome 8 and hence, decoding HCC from a ncRNAs perspective is mandatory emerging. 9 Increasing evidence suggests that lncRNAs are not only involved in gene expression regulations but also implicated in several biological and pathological processes, such as tumor development and its progression. 10 New research findings have revealed that the dysregulation of lncRNA expression contributes to the developing HCC and the subsequent formation of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells at the TME have a fundamental role in the development and progression of HCC [13] . Immune escape phenomena of HCC have recently been associated with a lot of obstacles and failures when it comes to the incorporation of the novel immune therapeutic approach in the treatment protocols of HCC patients [14] . Tumor cells dodge the normal immune screening and killing capacities through intricate genetic and epigenetic manipulations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%